PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DAN BERBICARA PADA SISWA SEKOLAH DASAR - Rachmadani, Isnie Nendita (2014)
The research motivated by the lack of ability of the students in learning to identify the story. The students have never been studied using audio-visual media at all, the previous of learning done in monotonous that makes students feel bored. The teacher were teaches with lecture method, so that learning to listen is ineffective and not efficient if the story is delivered by read by the teacher. In learning to speak, students are not completely be able to develop words when he recounted the story that told by the teacher, and most students are still shy to speak up in the class. The aim of this study are (1) describe the planning by the teacher in learning of Indonesian in identifying the subject of the story elements using the audio-visual media in the 5th grade Public Elementary School 3 Cibogo. (2) describe the implementation of a teacher in learning Indonesian language by using audio-visual media to improving learning outcomes on listening and speaking skills in identifying the subject of the story elements in 5th grade Public Elementary School 3 Cibogo. (3) describe the learning outcomes of students in 5th grade Public Elementary School 3 Cibogo especially in listening and speaking skills in identifying the subject of the story elements after learning using the audio-visual media. The method used in this study was Classroom Action Research (CAR), which adapted by the model Kemmis & Mc. Taggart. The subjects of research is students of 5th grade Public Elementary School 3 Cibogo District Lembang West Bandung Regency, which amount to 27 students. The research results using audio-visual media in learning of Indonesian shows an increase in the learning process, especially in listening and speaking, as seen from the increase in the results of each cycle, the average value of listening in students in the first cycle is 66.15, then second cycle becomes 81.95, and the third cycle becomes 86.36. And also in the student's speaking skills. In the first cycle of 30.76% which is the ability to speak well, second cycle becomes 73.91% which is the ability to speak well, on the third cycle increased to 77.27% which is the ability to speak well.